Postnasal drip and postnasal drip-related cough. Issue 1 (February 2016) - Yu, Jason L.; Becker, Samuel S.
Abstract : Purpose of review: This article describes the pathophysiology and management of postnasal drip (PND) with and without cough. Recent findings: PND is a common complaint in primary care and ear–nose–throat offices, and is often, but not always, associated with chronic cough. Because it lacks objective testing and its symptoms can be vague and variable, PND has become a catch-all diagnosis for a variety of nasal and throat-related symptoms. Studies have shown that the traditional pathophysiology of PND related to sinonasal disease does not clearly lead to chronic cough and that the cough from PND may be related to an airway sensory hypersensitivity rather than actual irritation from inflamed nasal secretions. Summary: The article summarizes the current recommendations on evaluation and management of PND as well as brings to discussion new therapies and hypothesis regarding its pathophysiology.